Iron ERRs with Salmonella - Fang, Ferric C. (2014)
The hormone hepcidin promotes iron sequestration by macrophages. A recent study by Kim et al (2014) implicates the orphan receptor ERRγ in the regulation of hepcidin production and suggests that targeting the ERRγ-hepcidin axis may be beneficial during infection with the facultative intracellular pathogen Salmonella.